Medical workers of health care institutions as a risk group for chemo-resistant tuberculosis: analysis of incidence, a clinical case. - N. S. Kolisnyk; A. I. Stadnik; D. V. Chabanenko; N. Y. Chebotar; Y. F. Savenkov; P. E. Bakulin (Medičnì Perspektivi)
The purpose of our study was to analyze the prevalence of morbidity of medical workers of health care institutions and anti-tuberculosis institutions, as well as the analysis of resistance of mycobacterium tuberculosis strains among medical personal of health facilities in the Dnipropetrovsk region. Retrospective analysis for 2015 - 2017 of electronic database of the patients register (TB-manager), outpatient cards and case histories of patients which underwent treatment in pulmonary-tuberculosis and surgical departments of CI «DnepropetrovskRegional Clinical Treatment and Prophylactic Association "Phthisiology"» DRC» was conducted . The incidence of tuberculosis among medical workers in health care institutions of Ukraine remains at a fairly high, stable level (426 cases of tuberculosis in 2016, 389 cases in 2017) on the background of the decrease in the incidence among the general population (59.5 people per 100 thousand population in 2014 and 51.9 per 100 thousand population in 2017 ). In Ukraine among tuberculosis patients – medical workers,  the overwhelming majority are workers of establishments of the general medical network (GMN) - 351 people, while in anti-tuberculosis institutions (ATI) in 2017, 38 cases of tuberculosis were registered. The article presents the clinical case of multidrug-resistant tuberculosis (MDR) in staff member of the pathoanatomical bureau, one of the medical institutions of the city Dnipro.